2019
DOI: 10.1242/bio.047175
|View full text |Cite
|
Sign up to set email alerts
|

Feedback loops in the Plk4–STIL–HsSAS6 network coordinate site selection for procentriole formation

Abstract: Centrioles are duplicated once in every cell cycle, ensuring the bipolarity of the mitotic spindle. How the core components cooperate to achieve high fidelity in centriole duplication remains poorly understood. By live-cell imaging of endogenously tagged proteins in human cells throughout the entire cell cycle, we quantitatively tracked the dynamics of the critical duplication factors: Plk4, STIL and HsSAS6. Centriolar Plk4 peaks and then starts decreasing during the late G1 phase, which coincides with the acc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…A priori, this is perhaps surprising, as Plk4 is often considered to be the master regulator of centriole biogenesis (Arquint and Nigg, 2016a;Bettencourt-Dias et al, 2005;Gönczy and Hatzopoulos, 2019;Habedanck et al, 2005). It has recently been shown that Plk4 can selforganise into liquid-like macromolecular condensates, and this self-organising ability has been hypothesised to be important for centriole biogenesis (Montenegro Gouveia et al, 2018;Park et al, 2019;Takao et al, 2019). Our observations demonstrate that Sas-6, Ana2 and Sas-4 also have a remarkable ability to self-organise into macromolecular structures that can recruit many other centriole and centrosome proteins, and this ability is independent of Plk4.…”
Section: Discussionmentioning
confidence: 99%
“…A priori, this is perhaps surprising, as Plk4 is often considered to be the master regulator of centriole biogenesis (Arquint and Nigg, 2016a;Bettencourt-Dias et al, 2005;Gönczy and Hatzopoulos, 2019;Habedanck et al, 2005). It has recently been shown that Plk4 can selforganise into liquid-like macromolecular condensates, and this self-organising ability has been hypothesised to be important for centriole biogenesis (Montenegro Gouveia et al, 2018;Park et al, 2019;Takao et al, 2019). Our observations demonstrate that Sas-6, Ana2 and Sas-4 also have a remarkable ability to self-organise into macromolecular structures that can recruit many other centriole and centrosome proteins, and this ability is independent of Plk4.…”
Section: Discussionmentioning
confidence: 99%
“…Cell culturing and immunofluorescence were previously described ( Takao et al , 2017 , 2019 ) and the details are as follows. NIH3T3 cells (ATCC) were cultured in DMEM supplied with 10% Fetal Clone III (Hyclone, GE Healthcare) and 1% penicillin/stereptomycin (Life Technologies, Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies proposed that Plk4 and STIL have an essential role in controlling centriole copy numbers by accumulating the essential components in a local focus around the mother centriole [19][20][21][22][23]. Mathematical models describing these focusing dynamics based on different mechanisms have been put forward [14,[23][24][25]. These models were formulated in terms of the local Plk4, STIL, and SAS-6 concentrations, which are continuous quantities untranslatable to discrete centriole numbers.…”
Section: Introductionmentioning
confidence: 99%